Is Continuous Passive Motion Therapy Useful in Improving the Health-Related Quality of Life Among Long-Term Immobilized Patients Following Trauma or Surgery? (International Journal of Physiotherapy, 2025)
Background: A continuous passive motion (CPM) device moves the joints passively when they are delicate to move by muscular forces due to pain and/or weakness. CPM is often applied in musculoskeletal issues to counter restriction of joint range of motion (ROM) and to prevent the development of hematomas and edema. CPM effectively reduces joint hemarthrosis and periarticular edema while enhancing hemarthrosis clearance. CPM effectively reduces joint hemarthrosis and periarticular edema while enhancing hemarthrosis clearance. CPM after knee arthroplasty accelerates motion recovery and protects against DVT and vascular issues.Methods: Based on the inclusion criteria, 48 subjects were selected for the study and allocated equally into two groups. Group A participants had undergone CPM therapy in addition to strengthening exercises of the lower limb, whereas Group B participants had continued conventional physiotherapy, i.e., knee mobilization and strengthening exercises, alternate days up to 3 weeks in a month for 6 months.Results: The average age of the individuals in groups A and B was 44.57±6.84 and 46.71±6.68 years, respectively. The mean change in VAS scores from baseline to the final assessment was also significantly more significant in group A [-2.68±0.73], [p=0.0.4661] compared to group B [-1.85±0.83], [p